The Effect of Administrative Accounting Functions on the Practices of the Higher and Central Administrations of the Economic Unit "An Applied Study on Joint Stock Companies" - الجبوري نصيف جاسم (Journal of Economics and Administrative Sciences, 2009)
Strategy Descrtibes How an Organization Matches its own Capabilites With Opportunities in Environment , in Order to Accomplish its Overall Objectives , So That The Organization is Considering Responding to Challenges by Adopting one or More of Strategies, Like Differentioning its Product, or Achieving Cost Leadership. The Key Role of Management Accountant is to Evlaute The Successful it Has Been in Implementing Organization Strategy. This Research Target to Explain The Key Role of Management Accountant in Evaluate of Organization Strategy. by Strategic Analysis of Operating Income From Specific Sources Such as Cost Savings and Growth in Stead of Emphasizing Only The Aggregate Change in Operating Income. The Problem of This Research is The Key Question , How Does Management Accountant Isolate Operating Income From Specific Sources ? and How Explain The Strategy Effect on Change of Operating Income ?. The Research Component of Four Chapters, The First, Whichis Contented of Whatis Strategy and The Second Focused on Strategic Analysis of Operating Income, The Third Focus on Analysis of Straegic Effect on Operating Income, The Last Focus on The Conclusions and Recommendations.